Plan anual de contrataciones y la eficiencia en las adquisiciones y contrataciones de la unidad de gestión educativa local de Loreto, Nauta 2023 - Torres Ramirez, Richard (2025)
This study was carried out basic, non-experimental and descriptive, to know the relationship between the annual contracting plan and the efficiency of acquisitions and contracting, a documentary analysis was used, in addition to a survey and as instruments a registration form was used. data and interview guide. The findings showed that the Contracting Annulment Plan and Efficiency in Acquisitions and Contracting have a very large perfect positive relationship, and that adding their significance (.000) the alternative hypothesis is rejected and the null is accepted. Implying that, if the Annual Contracting Plan were developed at a very high level, then acquisitions and contracting would be very efficient, which shows that the Annual Contracting Plan is significantly efficient in acquisitions and contracting.